(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2015)
Objective: The nutritional status of institutionalized elderly, their health behavior and related socio economic factors affecting their nutrition and feasibility of using red palm oil in the diets of inmates was investigated in present study. Methods: The sample comprised of 100 elderly from St. Mary’s Home Arya Mahila Ashram and Sandhya Home, New Delhi. The subjects were divided into 2 age groups namely 60-69 years and ≥ 70 years. The nutritional status was assessed using interview and observation method. The techniques employed were dietary survey, anthropometry, clinical examination, blood pressure, and hemoglobin and blood glucose measurement. The feasibility of using red palm oil was determined by sensory evaluation method. Results: The subjects had very strong food preferences and beliefs which affected their dietary intake. The mean daily of energy and other nutrients except iron and Vitamin ’A’ was adequate. Protein and retinol intakes were significantly different among residents of three institutions. The mean weight, height, mid upper arm circumference and total arm length for 60-69 years and ≥ 70 years men were 62.0kg, 156.8cm, 24.3cm, 63cm, 50.7cm and 63.1kg, 157.5cm, 25.3cm, 74.9cm and 52.3cm respectively. The corresponding values for woman were 61.8kg, 154.8cm, 25.7 cm, 81.3cm, 53cm and 56.4kg, 152.7cm, 24.2cm, 78.6cm, 51.4cm respectively. A significant correlation between the total arm length and height was observed. Six percent of the population was hypertensive 70% anemic and 49% had high blood glucose level. Red palm oil was well accepted by the inmates of St Mary Home when used in ’dhal’ vegetable preparation, "parantha" and suji halwa. Conclusion: The state of institutionalized elderly in the present study was good as institutions were taking care of at least their basic needs of food, clothing and shelter. A variety of programs like cultural, informative and interactive should be planned to keep them mentally and socially occupied. Since the elderly in the old age homes were having inadequate beta carotene, inclusion of foods like red palm oil by the management may be good idea.